IMPLEMENTASI METODE ROUND TABLE PADA PEMBELAJARAN BAHASA INGGRIS DI SMA N MLONGGO JEPARA - Alfia Nurmala (Intelegensia : Jurnal Pendidikan Islam, 2020)
AbstractThis research was conducted to find out the application of the round table method in learning English in SMA N Mlonggo Jepara. Besides, this research also aimed to find out the improvement in how active students during English learning process by using the round table method. This research was a classroom action research (CAR), which is research conducted in the classroom. The class action research model used in this study was the CAR model according to Kemmis and Mc Taggart which consists of four stages: planning, action, observation, and reflection. This study implements the Round Table method in English learning material Introduction in SMA Negeri 1 Mlonggo Jepara. The population of this study was class X IPS. Meanwhile, for the sample the researcher took class X IPS 1 as the sample. To analyze the data researchers used quantitative descriptive analysis techniques. The results showed that the round table cooperative learning method can improve the learning outcomes of Jepara 1 Mlonggo High School students in learning English "Introduction" material. This method can also increase student activity in following the teaching and learning process. Each cycle has increased, in the first cycle the average class obtained was 60.83 and the classical completeness achieved 30.5%. In the second cycle has increased. The class average increased by 26.67, the average class in the first cycle was 87.5. The increase in classical completeness from cycle I to cycle II reached 52.8%, classical completeness in cycle II reached 83.3%.Keywords: Learning Method; Cooperative Learning; Classroom Action Research; Round Table